Teletraffic call-level multirate loss models emphasizing on 4G/5G mobile networks - Παναγούλιας, Παναγιώτης (Πανεπιστήμιο Πελοποννήσου, 2023)
This thesis studies two mobile network links and proposes calllevel multiservice loss models that can be applied on them to calculate Call Blocking Probabilities and resource utilization. Analysis and simulation is about the X2 link of Long Term Evolution (LTE) networks and the downlink of an Orthogonal Frequency Division Multiplexing (OFDM) based cell. Starting from existing literature, this thesis proposes the analysis of the aforementioned links assuming new call arrival processes and several resource reservation policies. The used call arrival processes are: (i) Random calls – Random traffic (traffic originated via an infinite number of traffic sources), (ii) Quasirandom calls – Quasirandom traffic and (iii) Compound Poisson arrivals (traffic originated via a infinite number of traffic sources). The studied resource reservation policies are the: (i) Complete Sharing (CS), (ii) Bandwidth Reservation (BR), (iii) Multiple Fractional Channel Reservation (MFCR), (iv) Threshold (TH) and v) Threshold Call Admission (TCA). In the first two chapters, the X2 link of the LTE networks is examined (chapter 1) and three new loss models are proposed (chapter 2). In chapters 3 and 4 the downlink of an OFDMbased cell is examined (chapter 3) and three loss models under Poisson arrivals are proposed (chapter 4). Chapter 5 proposes three loss models for the OFDM cell regarding quasirandom call arrivals, while in chapter 6, two loss models under compound Poisson arrivals are proposed. Finally, in chapters 7 and 8 the threshold (TH) policy is analysed and a loss model under quasirandom arrivals assuming the Threshold Call Admission (TCA) policy is proposed. The accuracy of the proposed formulas for the determination of Call Blocking Probabilities and resource utilization has been verified via simulation and was found to be absolutely satisfactory.
Μοντέλα απώλειας πολλαπλών ρυθμών τηλεκίνησης σε επίπεδο κλήσεων με έμφαση στα δίκτυα κινητής τηλεφωνίας 4G/5G
Keywords: Συστήματα ασύρματων επικοινωνιών; Συστήματα κινητής επικοινωνίας; Τηλεπικοινωνιακή κίνηση; Ασύρματα δίκτυα; Συμφόρηση; Τυχαία κίνηση; Ψευδοτυχαία κίνηση; Πολιτική δέσμευσης εύρους ζώνης; Μοντέλο απωλειών; Αναδρομικός τύπος; Απώλεια κλήσεως; Φορτίο κίνησης; Wireless networks; Congestion; Random traffic; Quasi-random traffic; Bandwidth reservation policy; Loss model; Recursive formula; Call blocking; Traffic-load